Ultrasound guided percutaneous catheter drainage of an appendicular perforation with large intraperitoneal abscess formation: an effective modality of management in selected cases - Das, Deepak Kumar; Patra, Rajat Kumar; Mishra, Subhrajit; Panigrahi, Sudhir Kumar (International Surgery Journal, 2019)
Appendicular pathology is a very common entity and appendicular perforation can present in various forms ranging from right lower abdominal pain, fever and anorexia to frank peritonitis with endotoxaemic shock. We present a 18 year female with fever, anorexia and a large upper and mid abdominal swelling of 2 weeks duration which after admission was treated with intravenous fluids, antibiotics, analgesics and antiemetics. Her CECT abdomen and pelvis revealed a huge fluid containing cystic lesion with a perforated appendix tip and intraluminal faecolith and calculi. She underwent USG guided 10F pigtail catheter drainage of the walled off peritoneal collection on 3rd day of admission. About 700 ml of serous fluid with minimal flecks was drained within 2 hours and another 860 ml over next 3 days. The pigtail drain was removed on day 7 and she was discharged on day 9, with USG abdomen confirmation of complete disappearance of the abdominal collection. Ultrasound guided percutaneous catheter drainage of the appendicular abscess with IV antibiotics cures the patient in selected case scenario.